Unruptured intracranial aneurysm presenting with epiletic seizure - José C. Sena; Yves Reynier; Bernard Alliez (Arquivos de Neuro-Psiquiatria)
Intracranial aneurysms are frequently present with subarachnoid hemorrhage.Less often they produce suggestive symptoms of cranial nerve dysfunction or intracranial tumor when very large. Their association with epilepsy has rarely been reported; such concurrence may not be a coincidence. When the patient presents with epileptiforme attacks the presence of an intracranial aneurysm is rarely considered. In this paper we report the case of a 45-years-old patient with an unruptured aneurysm of the middle cerebral artery with a 10 years history of epileptic seizure.